Postmodern Border Crossings – Metalepsis as a Symptom of Contemporary Culture (KULT_online, 2011)
Based on the definition of the term metalepsis coined by Gérard Genette in 1972, Sonja Klimeks book on Paradoxes Erzählen: Die Metalepse in der phantastischen Literatur (Paradox Narration: Metalepsis in Fantastic Literature) attempts a categorisation and a cultural studies analysis of paradoxical phenomena in various narrations. On the one hand it offers a description and definition of narratological terms, and on the other a comparatistic and interdisciplinary approach to paradoxical narratological phenomena, wherein metalepsis is to be contextualised with the findings of philosophical and epistemological cultural studies as a contemporary cultural symptom. Because of its irritatingly wide range of argumentations and scientific methods, the study turns out to be a rather heterogeneous piece of work.